Implementation of E-Learning and Normative Commitments Towards the Performance of Kpps Members (Voting Organizing Group) in the 2024 Elections in Cirebon Regency - Anis Ni'Matul Maula; Geby Aditiya Damayanti; Sandi Nasrudin Wibowo (PT FORMOSA CENDEKIA GLOBAL, 2024)
In performance, it is very important to pay attention to things that need to be supported in order to improve and provide maximum work results. Then from this the researcher conducted a research which was very interesting to research, the research conducted by the researcher analyzed how the implementation of E-learning and Normative Commitment affected the performance of KPPS (Voting Organizing Group) members in the 2024 elections in Cirebon Regency. This research aims to find out whether E-learning and Normative Commitment have an effect on the performance of KPPS (Voting Organizing Group) members in the 2024 elections in Cirebon Regency. The data search was carried out by researchers by distributing questionnaires to KPPS members in Cirebon Regency and this research used quantitative research methods. The population in this study were members of the KPPS (Polling Organizing Group) in Cirebon Regency, the sample taken was 130 respondents. In this study, the data was processed using SPSS version 22. The data was tested using validity and reliability tests for questionnaires and multiple linear regression analysis with t-test and f-test to prove the hypothesis. The research results show that E-learning has a positive and significant effect on Performance, Normative Commitment has a positive and significant effect on Performance, and the two variables between E-learning and Normative Commitment both have a positive and significant effect on Performance.